Carbon Emission Disclosure, Carbon Performance, and Green Intellectual Capital : Their Influence on Firm Performance with Firm Size as a Moderator (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
This study aims to examine the influence of carbon emission disclosure, carbon performance, and green intellectual capital on firm performance, with firm size as a moderating variable. The research focuses on companies in the basic materials sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The data collection technique employed is documentation, using data obtained from the official website of the Indonesian Stock Exchange. A total of 93 companies were selected as the research sample through purposive sampling. Multiple linear regression and moderated regression analysis (MRA) were used for data analysis. The results reveal that only carbon performance significantly influences firm performance, with a significance value of 0.000 (less than 0.05) and a T-statistic of 3.771 (greater than the T-table value of 1.66196). In contrast, carbon emission disclosure and green intellectual capital showed no significant effects on firm performance, with significance values of 0.576 and 0.543, respectively, and T-statistics of -0.561 and 0.610. Furthermore, the MRA results indicate that firm size does not moderate the relationship between carbon emission disclosure, carbon performance, and green intellectual capital on firm performance, with significance values of 0.757, 0.679, and 0.399, all greater than 0.05. These findings suggest that while carbon performance has a direct effect on firm performance, carbon emission disclosure and green intellectual capital do not appear to influence performance significantly in the context of Indonesian companies in the basic materials sector. The role of firm size as a moderator is also not supported by the data.